Perlidungan Hukum Justice Collaborator Dalam Tindak Pidana Pembunuhan Berencana: Studi Putusan Nomor 798/Pid.B/2022/PN.Jkt.Sel. - Syabilal Ali; Irwan Triadi (Deposisi: Jurnal Publikasi Ilmu Hukum, 2024)
The world history of Justice Collaborators began in 1963 when the United States federal government awarded facilities or awards to a winner named Joe Cago. Cago was a member of a criminal organization whose members were Italian immigrants or descendants of Italians living in the country. The reason is, every member of this criminal organization who is arrested will still uphold omerta, or the culture of silence in the mafia network, and they never leak information about their organization to the authorities, making it difficult for the authorities. The research method used is normative juridical. The use of this type of normative juridical research is because the object of study is related to legal principles and principles as well as theories and opinions of legal experts. Criminal Law that include Justice Collaborators in criminal activities are inadequate, so that law enforcement officials cannot legally rely on this system. It turns out that there are many things that need to be set aside to achieve justice collaborator status, in terms of relevance. Many legal experts have expressed the same thing, the use of justice collaborator status is only to show appreciation for criminals who actively participate in cases that are difficult to prove.